2018
DOI: 10.1007/s12012-018-9480-0
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cardiomyopathy Due to Arthroprosthetic Cobaltism: Report of Two Cases with Different Outcomes

Abstract: Cobalt-induced cardiomyopathy is a well-known but uncommon disease, and the physician must maintain a high index of suspicion in order to make a timely diagnosis. We report two patients with cobalt-induced cardiomyopathy. Both patients developed progressively worsening symptoms of cobalt toxicity following revision of a fractured ceramic-on-ceramic total hip replacement to a metal-on-polyethylene bearing. In both patients, echocardiography showed LV hypertrophy, biventricular systolic dysfunction, and a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…CoNPs produced by the reduction or wear of internal plants are first deposited around the internal fixation plate and artificial joint prosthesis to cause inflammatory pseudotumor around the implant, loosening of the prosthesis, as well as local osteoporosis. Meanwhile, due to their nano-size effect, CoNPs are more likely to enter into the blood and lymphatic system, followed by their broad distribution in multiple organs or tissues of the human body through systemic circulation, resulting in different adverse symptoms [4][5][6][8][9][10][11]. Therefore, the patients undergoing MOM joint replacement need to be monitored and detoxified.…”
Section: Introductionmentioning
confidence: 99%
“…CoNPs produced by the reduction or wear of internal plants are first deposited around the internal fixation plate and artificial joint prosthesis to cause inflammatory pseudotumor around the implant, loosening of the prosthesis, as well as local osteoporosis. Meanwhile, due to their nano-size effect, CoNPs are more likely to enter into the blood and lymphatic system, followed by their broad distribution in multiple organs or tissues of the human body through systemic circulation, resulting in different adverse symptoms [4][5][6][8][9][10][11]. Therefore, the patients undergoing MOM joint replacement need to be monitored and detoxified.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen cases were included in the probable group [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23] based on the presence of either cardiac histopathology or cobalt systemic toxicity features and evidence of pre-existing risk factors for CMP (Table 3). Mean blood cobalt level was 425 ppb (range 112-1556).…”
Section: Resultsmentioning
confidence: 99%
“…Chelation therapy was initiated in 7 cases upon a diagnosis of cobalt toxicity which led to a reduction in blood cobalt concentrations, but required additional measures for clinical improvement including hip revision and cardiac function support. Different types of therapies used include N -acetyl-cysteine [26], 2,3-dimercaptopropane-1-sulfonate [18], and ethylene diamine tetra-acetic acid [17].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, elevated cobalt levels presumably cause hypothyroidism, at times associated with goitre and myxoedema [1,17]. It is important to note that, according to the current literature, effects on both cardiac and thyroid function as well as neurological deficits appear to be at least partially reversible, provided cobalt exposure is promptly stopped or significantly reduced [1,7,21,22].…”
Section: Cobaltmentioning
confidence: 96%
“…The literature on the cardiotoxic potential of cobalt is inconsistent. Whereas some studies found no significant metal-associated cardiovascular morbidity in patients with joint prosthesis/es and elevated systemic cobalt levels [18,19], others have reported severe dilatative cardiomyopathy, often associated with pericardial effusion and significantly reduced left ventricular ejection fraction, or found significantly elevated myocardial cobalt concentrations, cardiomegaly and interstitial fibrosis in the course of histo-/pathological investigations [1,5,7,17,20,21]. Moreover, elevated cobalt levels presumably cause hypothyroidism, at times associated with goitre and myxoedema [1,17].…”
Section: Cobaltmentioning
confidence: 99%